Polynomials with exponents in compact convex sets and associated weighted extremal functions – Generalized product property - Snorrason, Bergur (MATHEMATICA SCANDINAVICA, 2024)
A famous result of Siciak is how the Siciak-Zakharyuta functions, sometimes called global extremal functions or pluricomplex Green functions with a pole at infinity, of two sets relate to the Siciak-Zakharyuta function of their cartesian product. In this paper Siciak’s result is generalized to the setting of Siciak-Zakharyuta functions with growth given by a compact convex set, along with discussing why this generalization does not work in the weighted setting.